2014
DOI: 10.2166/wst.2014.391
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Zn2+ and Ni2+ in a binary aqueous solution by biosorbents derived from sawdust and water hyacinth (Eichhornia crassipes)

Abstract: The Zn(2+) and Ni(2+) adsorption capacities of six biosorbents derived from water hyacinth (Eichhornia crassipes) (WH) and sawdust (SD) were investigated, with activated carbon as the control. The biosorbents were raw biomass (WH, SD), charred WH (BWH) and SD and sulphonated bio-chars of WH and SD. The effect of the initial solution pH and Zn(2+) and Ni(2+) concentrations on adsorption capacity was studied, and adsorption isotherms for Zn(2+) and Ni(2+) evaluated. The initial solution pH significantly influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…Adsorption data following the Langmuir model indicate homogeneous monolayer or surface adsorption of Zn 2+ and Pb 2+ on the SWPS resins, while those that followed the Freundlich isotherm model suggest multilayer adsorption or the occurrence of both surface and intra-particle diffusion. Similar behaviour has been reported for sulphonated biochar [18]. This confirms the insertion of sulphonic groups, which improve the adsorption capacity of the waste polystyrene.…”
Section: Adsorption Isothermssupporting
confidence: 87%
See 3 more Smart Citations
“…Adsorption data following the Langmuir model indicate homogeneous monolayer or surface adsorption of Zn 2+ and Pb 2+ on the SWPS resins, while those that followed the Freundlich isotherm model suggest multilayer adsorption or the occurrence of both surface and intra-particle diffusion. Similar behaviour has been reported for sulphonated biochar [18]. This confirms the insertion of sulphonic groups, which improve the adsorption capacity of the waste polystyrene.…”
Section: Adsorption Isothermssupporting
confidence: 87%
“…This suggests sulphonated EPS has a higher concentration of inorganics, this could account for the lower adsorption capacity for both Pb 2+ and Zn 2+ . Both these EC values were however, lower than those of biosorbents derived from water hyacinth and sawdust which were in the ranges 103-173.2 and 2.3-3.9 mS/m respectively [18]. The water content of sulphonated HIPS is slightly higher (about 5.79%) than that of sulphonated EPS.…”
Section: Physicochemical Characterisationmentioning
confidence: 67%
See 2 more Smart Citations
“…Gwenzi et al (2014) also found that the affinity order Cd(II) [ Cu(II) found in mono solute solutions changed to Cu(II) [ Cd(II) when the metals were forming binary mixtures. As seen in Table 6, the sum of the maximum adsorption values of both metals in binary mixtures (q max , tot ) is in most of the cases less than the sum of those in single solutions indicating that the joined effect on each other metal is antagonistic.…”
Section: Discussionmentioning
confidence: 91%